Mujadalah Ahsan Counseling Model to Overcome Mental Health Disorders of BKPI Final Year Students at PTKIN Sumatera - Safri Mardison; Jum Anidar; Suryadi Fajri; Ilhamdi Yusra; Aulia Rahmi Putri (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to develop an Islamic counseling model of Mujadalah Ahsan to overcome mental health problems (mental illness) in final year students of the Islamic Education Counseling Guidance Study Program (BKPI) at State Islamic Religious Universities (PTKIN) in Sumatra. Final-year BKPI students often face academic, social, and personal pressures that can trigger mental health disorders. The Mujadalah Ahsan model proposed in this study integrates Islamic counseling principles with a good and wise communication approach (ahsanu mujadalah), by the teachings of the Qur'an. The research method used is research and development (R&D), which involves needs analysis, model development, validation test by experts, and implementation in the field. Data were collected through in-depth interviews, observations, and questionnaires distributed to students and BKPI supervisors at PTKIN. The results showed that the Mujadalah Ahsan Islamic counseling model is effective in helping students overcome problems of anxiety, depression, and academic pressure through a harmonious spiritual and psychological approach. This model also contributes to developing Islamic counseling theory and practice that is more relevant in the context of Islamic higher education and enriching alternative approaches in dealing with mental health in students. Thus, this model is hoped to be implemented more widely in various PTKIN in Indonesia to support students' mental well-being.